Fluorinated polymerizable phosphonium salts from PH3: Surface properties of photopolymerized films. Issue 13 (19th April 2013) - Guterman, Ryan; Berven, Bradley M.; Chris Corkery, T.; Nie, Heng‐Yong; Idacavage, Mike; Gillies, Elizabeth R.; Ragogna, Paul J.
ABSTRACT An array of highly fluorinated polymerizable phosphonium salts (HFPPS) were synthesized from PH3 and utilized in UV‐curable formulations. Inclusion of these salts at very low loading (0.1–1 wt %) into hexanediol diacrylate (HDDA) resulted in hydrophobic surfaces. The water repellency was achieved with short C4F9 fluorocarbon appendages in the monomer as opposed to the bioaccumulative C8F17 appended polymers. The physical properties of these new monomers were also characterized. The molecular architecture of the monomers had a pronounced effect on both their physical properties along with the degree of hydrophobicity imparted in the polymer. Salts utilizing the bis(trifluoromethylsulfonyl)imide anion displayed excellent compatibility with HDDA, while the chloride salts were insoluble. Time‐of‐flight secondary ion mass spectrometry (TOF‐SIMS) confirmed the presence of the HFPPS at the surface of the polymer coating. For the first time this demonstrates how these salts may be used to functionalize the surface of a UV‐cured film with ionic species. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 2782–2792